2003
DOI: 10.1111/j.1346-8138.2003.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Scabies Mimicking Bullous Pemphigoid

Abstract: Scabies is an infestation caused by Sarcoptes scabiei and characterised by polymorphous lesions that may include burrows, papules, nodules, excoriation and crusts. Vesicular and bullous lesions are rather rare. Several diseases may be confused with scabies. We report a case of bullous scabies which, on the basis of the clinical and histopathological picture, mimicked bullous pemphigoid. Direct and indirect immunofluorescence were negative. Bullae recurred and persisted despite systemic corticosteroids. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Scabies has multiple presentations and has been reported by numerous studies to mimic pemphigoid . One such atypical manifestation most common among the elderly are bullous lesions known as bullous pemphigoid‐like eruptions .…”
Section: Discussionmentioning
confidence: 99%
“…Scabies has multiple presentations and has been reported by numerous studies to mimic pemphigoid . One such atypical manifestation most common among the elderly are bullous lesions known as bullous pemphigoid‐like eruptions .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it is difficult to distinguish between bullous pemphigoid and scabies with bullous pemphigoid symptoms, especially when the skin scrapings do not reveal any mites or eggs 3 . Even when the skin scrapings are positive, there is still the possibility of scabies and concomitant bullous pemphigoid to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations have been given in the published work about the pathophysiology of blister formation in these atypical cases of scabies. One author suggested that the mites or their lytic secretions may cause the alteration or the release of bullous‐pemphigoid‐antigen (BP antigen), leading to an immunological response and resulting in the production of anti‐basement membrane zone antibodies, as seen in bullous pemphigoid 3 . Another author speculated that the mite itself may act as an antigen which cross‐reacts with the BP antigen to stimulate the production of autoantibodies, 11 but neither explanation is complete and further evaluation is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developed countries the differential diagnosis should include common pruritic dermatoses such as psoriasis, atopic eczema and lichen planus. If blistering is present, then bullous pemphigoid [45, 46] and dermatitis herpetiformis should be considered. Additionally, there appears to be an increased risk of developing psoriasis following scabies [47].…”
Section: Treatmentmentioning
confidence: 99%